SUPPLY CHAIN MANAGEMENT IN THE FOOD INDUSTRY: A COMPREHENSIVE HIERARCHICAL DECISION-MAKING STRUCTURE - M.Gusarova, Olga; E.Yerzhanova, Mira; S.Berezniak, Irina; A.Konstantinov, Viktor; A.Vityutina, Tatyana (International Journal of Supply Chain Management, 2019)
in the new economic management conditions, the existing models of supply chains in the food industry cannot meet current realities. This makes it relevant to develop models and algorithms for supply chain management, design and use various alternative configurations in order to achieve efficiency and competitive advantages. The proposed algorithm and methodological support for modeling supply chains in the food industry are based on the commodity flow classification according to the importance of resources and take into account modern methods and concepts of logistics. Our research deals with the current problems in supply chain management, production planning, supply and transportation, warehouse management and vehicle selection to maximize the logistics efficiency in the supply chain.The purpose of our research is to study the existing problems in the food supply chain management and to propose a decision-making algorithm for efficient and competitive business development. The study and generalization of theoretical studies in the field of food supply chain management allowed us to identify and formulate the specifics of this industry with the help of the following research methods: selection of logistics intermediaries, forecasting (indicators, flows, etc.), arrangement of nomenclature groups, optimization under risk conditions, statistical methods in data processing.Based on the research results and the methods described in it, a supply chain management algorithm is proposed. It will provide optimization and control in supply chain management. An algorithm for systematizing and efficient management of the supply chain of the â??Klinskyâ? meat-packing plant is also suggested.